Angiotensin II Type 1 Receptor Blockade Prevents Lethal Malignant Hypertension - Hilgers, Karl Friedrich; Hartner, Andrea; Porst, Markus; Veelken, Roland; Mann, Johannes (Circulation, 2001)
Background— Angiotensin II is elevated in malignant hypertension. We tested the hypothesis that angiotensin II type 1 receptor blockade can prevent the development of malignant hypertension even in the absence of a blood pressure-lowering effect. Methods and Results— Two-kidney, 1-clip rats were followed up for 28 days; blood pressure was measured by tail-cuff plethysmography and intra-arterially. After a 2-week run-in phase, rats received valsartan at a dose of 0.3 (n=14) or 3 (n=12) mg · kg−1 · d−1 or solvent (n=27). Only the higher dose of valsartan, but not the lower dose, decreased blood pressure. Both doses of valsartan prevented the development of lethal malignant hypertension. Twenty of 27 solvent-treated renovascular hypertensive rats died, but only 3 of 14 rats treated with the low dose and 1 of 12 rats treated with the high dose of valsartan died. Histological signs of malignant nephrosclerosis were found in all rats examined that had died throughout the study and in 6 of 7 surviving solvent-treated renovascular hypertensive animals. Increased expression of monocyte chemoattractant protein-1 and prominent interstitial influx of macrophages occurred in the nonclipped kidneys exposed to high pressure in solvent-treated rats. These alterations were prevented by valsartan at both doses, irrespective of blood pressure effects. Conclusions— Angiotensin II type 1 receptor blockade by valsartan prevents lethal malignant hypertension independently of blood pressure. The results suggest that reduction of angiotensin-induced inflammation in the kidney may contribute to the protective effects of valsarta
Keywords: angiotensin; hypertension; kidney; leukocytes; survival